Influence radius of pressure relief of energy-accumulating blasting and water injection in the heading face of the liangbei coal mine - Wang, Zhenfeng; Wang, Yu; Wang, Feng (Frontiers in Earth Science, 2023)
This study aims to reasonably determine the influence radius of pressure relief of energy-accumulating blasting and water injection in the Liangbei Coal Mine and effectively eliminate local stress concentration and coal seam outburst risk. The change in gas parameters in each test hole before and after ener-gy-accumulating blasting and water injection is determined through ANSYS/LSDYNA numerical simula-tion, theoretical analysis and calculation, and the application of the gas parameter method in the 32051 heading face of the Liangbei Coal Mine. The influence radius of pressure relief technology of ener-gy-accumulating blasting and water injection in the Liangbei Coal Mine in the direction of ener-gy-accumulating trough is studied, which provides reliable data for the layout parameters of ener-gy-accumulating blasting and water injection hole in the working face of the Liangbei Coal Mine. The ex-perimental results are as follows: (1) The simulation via ANSYS/LSDYNA shows that a blasting cavity is formed by an explosive shock wave in the borehole. The diameter of the blasting cavity in the ener-gy-accumulating direction is 42 cm, which is 10 times the diameter of the energy-accumulating blasting and water injection hole. The diameter of the blasting cavity in the non-energy-accumulating direction is 14 cm, which is 3.3 times the diameter of the energy-accumulating blasting and water injection hole. The stress in the energy-accumulating direction is 2.9 times larger than that in the non-energy-accumulating direction. The crack length in the energy-accumulating direction is 2.94 m, and the crack length in the non-energy-accumulating direction is 0.8 m. (2) Theoretical analysis and calculation present that the crushing area of shaped charge blasting is 0.39 m, the fracture area is 2.67 m, and the vibration area is 1.59 m. (3) Comparison of the change in gas parameters of each test hole in the field experiment before and af-ter energy-accumulating blasting and water injection indicates that the influence radius of pressure relief in the direction of energy-accumulating trough is 3 m.